An enhanced state convergence architecture incorporating disturbance observer for bilateral teleoperation systems. (9th October 2019) - Asad, Muhammad Usman; Farooq, Umar; Gu, Jason; Balas, Valentina E; Abbas, Ghulam; Balas, Marius; Muresan, Vlad
To bilaterally control an n th-order teleoperation system modeled on state space, state convergence methodology provides an elegant way to design control gains through a solution of 3 n + 1 equations. These design conditions are obtained by allowing the master–slave error to evolve as an autonomous system and then assigning the desired dynamic behavior to the slave and error systems. The controller, thus obtained, ensures the motion synchronization of master and slave systems with adjustable force reflection to the operator. Although simple to design and easy to implement, state convergence method suffers from its dependence on model parameters, and thus the performance of the controller may degrade in the presence of parametric uncertainties. To address this limitation, we propose to integrate an extended state observer in the existing state convergence architecture which will not only compensate the modeling inaccuracies by treating them as a disturbance but will also provide the estimates of the master and slave states. These estimated states are then used to construct the bilateral controller which is designed by following the method of state convergence. In this case, 2 n + 2 additional design equations are required to be solved to fix the observer gains. To validate the proposed enhancement in the state convergence architecture, simulations and semi-real-time experiments are performed in MATLAB/Simulink environment on a single degree-of-freedom teleoperation system.